Living the Curriculum Review: Perspectives from Three Leaders - Lock, Jennifer; Hill, S. Laurie; Dyjur, Patti (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2018)
A requirement for quality assurance is becoming more prevalent in higher education today as institutions are being asked to demonstrate that they are providing robust, meaningful learning experiences for students. Many institutions are adopting curriculum review frameworks as part of their overall quality assurance strategy. Three leaders at various levels who were engaged in a year-long curriculum review process share reflections about their experiences and challenges while conducting an undergraduate program review. Their theoretical framework for an effective curriculum review process is shared in this paper. The leaders offer institutional, faculty, and course level insights, and make five recommendations for a collaborative curriculum review process: (1) setting clear expectations; (2) maintaining open, consistent communication; (3) incorporating multiple levels of leadership; (4) engaging various groups of stakeholders; and (5) implementing through actionable items.